Artisanal and controlled pyrolysis-based biochars differ in biochemical composition, thermal recalcitrance, and biodegradability in soil. (January 2016) - Jegajeevagan, K.; Mabilde, L.; Gebremikael, M.T.; Ameloot, N.; De Neve, S.; Leinweber, P.; Sleutel, S.
Abstract: Biochar composition and stability is under intense research. Yet the question remains to what extent the current state-of-the-art applies to artisanally charred biomass in tropical regions. We compared kiln and drum based biochars with their counterpart controlled (at 400 °C) slow pyrolysis biochars from coconut shells, rice husks and Palmyra nutshell for their biochemical composition, thermal stability and biodegradability in soil. Thermal behavior of individual organic constituents was quantified by pyrolysis-field ionization mass spectroscopy (Py-FIMS). Comparison of the mass spectra demonstrated higher abundances of either phenols, lignin and carbohydrate monomers or of lipids in the artisanally produced biochars. Hence, relatively more untransformed plant matter was preserved by artisanal charring and also the thermal stability of carbohydrates, alkylaromatics and N-containing compounds was lower for all three feedstocks. This indicates lower prevailing temperatures compared to controlled pyrolysis biochar, at least in parts of the biomass charring in the kilns or drum. Nine-weeks biochar derived C mineralization upon soil incorporation revealed a relatively lower biological stability of the controlled pyrolysis biochars. The proportion of detected ion intensity from thermolabile lower mass signals (<400 °C, m/z  < 250) was negatively correlated to the net-biochar derived C mineralization. We hypothesize this fraction to be composite and act both as a C-substrate and at the same time to hold unidentified substances inhibiting microbial activity. Compared to controlled pyrolysis biochar, traditionally charred biomass, i.e. the 'biochar' most likely to be actually applied to soil in developing countries, has a heterogeneous thermal and biochemical composition and unpredictable biological stability. Highlights: Artisanal chars are biochemically and thermally more heterogeneous than biochars. Untransformed plant matter is relatively more present in artisanally produced biochar. Spatial heterogeneity of temperature in kilns or drums may explain this larger variation. Content of thermolabile low mass building blocks explained lower biodegradability. We hypothesize this fraction to be composite and hold inhibitory substances as well.